Effects of Connecting Structures in Double-Hulled Water-Filled Cylindrical Shells on Shock Wave Propagation and the Structural Response to Underwater Explosion - Caiyu Yin; Zhiyang Lei; Zeyu Jin; Zifeng Shi (Journal of Marine Science and Engineering)
In conventional double-hulled submarines, the connecting structures that facilitate the linkage between the two hulls are crucial for load transmission. This paper aims to elucidate the effect of these connecting structures on resistance to shock waves generated by underwater explosions. Firstly, a self-developed numerical solver is built for the one-dimensional water-filled elastically connected double-layer plate model. The shock wave propagation characteristics, shock response of structure, water cavitation, and impact loads transmitted through the gap water and the connecting structures are analyzed quantitatively. The results reveal that the majority of the shock impulse is transmitted by the gap water if the equivalent stiffness of the connecting structures is much less than that of the gap water. Then, a three-dimensional model of the double-hulled, water-filled cylindrical shell is constructed in Abaqus/Explicit, utilizing the acoustic-structural coupling methodology. The analysis focuses on the influence of the thickness and density distribution of the connecting structures on the system’s shock response. The results indicate that a densely arranged connecting structure results in a wavy deformation of the outer hull and a notable reduction in both the impact response and strain energy of the inner hull. When the stiffness of the densely arranged connecting structure is comparatively low, the internal energy and plastic energy of the inner hull are decreased by 16.5% and 24.1%, respectively. The findings of this research are useful for assessing shock resistance and for the design of connecting structures within conventional double-hulled submarines.